Asymmetric Cell Division in Polyploid Giant Cancer Cells and Low Eukaryotic Cells - Zhang, Dan (Hindawi Publishing Corporation, 2014)
Asymmetric cell division is critical for generating cell diversity in low eukaryotic organisms. We previously have reported that polyploid giant cancer cells (PGCCs) induced by cobalt chloride demonstrate the ability to use an evolutionarily conserved process for renewal and fast reproduction, which is normally confined to simpler organisms. The budding yeast, Saccharomyces cerevisiae, which reproduces by asymmetric cell division, has long been a model for asymmetric cell division studies. PGCCs produce daughter cells asymmetrically in a manner similar to yeast, in that both use budding for cell polarization and cytokinesis. Here, we review the results of recent studies and discuss the similarities in the budding process between yeast and PGCCs.